Bleach. 15, Beginning of the death of tomorrow - Kubo, Tite (Kubo, Tite. Bleach (VIZ Media), 2006)
During a bloody confrontation with a sadistic Soul Reaper, Uryû chooses a path that will temporarily grant him enormous power, at great personal cost. Meanwhile, Ichigo races to master a powerful technique that will help him fight Byakuka and,hopefully, save Rukia from execution.